Relocation Policy in Indonesia to Achieve Sustainable Community Life: in Review - Westi Utami (Sumatra Journal of Disaster, Geography and Geography Education, 2026)
The occurrence of natural disasters frequently results in the impairment of settlements, thus rendering relocation the optimal course of action. The present study aims to review relocation policies and recovery efforts following the Aceh tsunami, the eruptions of Mount Merapi in Yogyakarta and Mount Sinabung, and the disaster in Central Sulawesi. The research was conducted using a descriptive qualitative approach. The research findings highlight significant challenges in relocation, including the difficulty of securing land that is physically and legally clean and clear. In order to address these issues, land provision was carried out using village land, state land, land with cultivation rights, and the release of production forest areas. The review also indicates that in order to support livelihood sustainability, the government implemented several strategies, including the provision of agricultural land in Sinabung, the utilisation of KRB III land as a livelihood source in Yogyakarta, and the facilitation of new job opportunities for the community. This review underscores that the challenges associated with relocation extend beyond the mere procurement of land and the establishment of settlements, encompassing the imperative of restoring community livelihoods. The findings of this study are expected to provide a foundation for the formulation of appropriate relocation policies in the future, ensuring that communities are safe from disasters and able to live more prosperously.